Microfluidic Generation of Monodisperse and Photoreconfigurable Microspheres for Floral Iridescence–Inspired Structural Colorization. Issue 26 (6th May 2016) - Yeo, Seon Ju; Park, Kyung Jin; Guo, Kai; Yoo, Pil J.; Lee, Seungwoo
Abstract : Flowering plants have evolved their structural coloration strategies exquisitely to split various vivid colors into a spatially distributed sequence by using the 2D diffraction elements, confined onto a curved surface. Herein, A new strategy of artificially mimicking floral‐inspired grating diffractive motifs onto the monodisperse and smooth microspheres is reported, developed by microfluidics; thus, the accessible design space of structural colorization can be greatly expanded.